TEACHERS' STRATEGIES IN TEACHING GRAMMAR TO YOUNG LEARNERS : A Case Study At Six Elementary Schools In Bandung - Pratiwi, Santi Dian (2011)
This study was conducted to investigate the strategy used by the teachers in teaching grammar to young learners, the obstacle arisen in the process of teaching, and the solution to the problem encountered. The study employed a qualitative research method. The participants of this study were six teachers from six elementary schools both upper level and lower level. The data were obtained from several sources including class observation and interview. The findings reveal that most of the teachers rarely prepared the lesson plan, and all of them always prepared the material. Two of them also prepared the teaching media. In relation to the strategies used in teaching grammar to young learners, the teachers used various strategies: teaching grammar from rules (deductive approach), teaching grammar from examples (inductive approach), and teaching grammar through texts. Deductive approach was the strategy mostly used by the teachers. In relation to assessment, the teachers used several types of assessment such as grammar practice which included role plays, written exercises and homework, and quizzes. In relation to the problems, several teachers had problems in planning the lesson, preparing the material, implementing the grammar teaching, but they had been able to solve their problems. Based on the findings, it is recommended that the teachers of young learners should plan the lesson before teaching in order to make the lesson run smoothly. Besides, they also should vary the teaching methods in order to make teaching and learning more interesting and effective. In relation to the assessment, the teachers should give the assessment not only in the form of written exercises or tests, but also in the form of communication such as conversation or dialog, in order to make the students able to use grammatical rules in the real-life context.